Attentional Disengagement Deficits Predict Brooding, but Not Reflection, Over a One-Year Period - Allard, Eric S.; Yaroslavsky, Ilya (Frontiers in Psychology, 2019)
A growing literature suggests that rumination is linked to attentional control deficits in depression. This is particularly the case with brooding, a maladaptive form of rumination. However, research on the potential constructive association between attentional control and self-reflection, a putative adaptive form of rumination, is sparse. Thus, the goal of the present study was to examine whether attentional control deficits, indexed via visual attentional disengagement, differentially predict dispositional brooding and self-reflection tendencies. Depressed participants (n = 17), those in remission from depression (n = 42), and their peers with no depression histories (n = 70) completed clinical interviews, the Ruminative Response Scale (RRS), and an eye-tracking task that measured attentional disengagement from pleasant (happy) and unpleasant (sad) facial images during a laboratory visit, and the RRS at four-month intervals over a one-year period. Results revealed that slow disengagement from sad faces, and rapid disengagement from happy faces, was specifically associated with brooding tendencies concurrently and across follow-up. Attentional disengagement was unrelated to self-reflection. The disengagement-brooding associations remained after controlling for depression status and anxiety disorder histories, suggesting that attentional control deficits may be a state-independent marker of brooding. Theoretical and clinical implications for these associations are discussed.